Length-weight relationship and relative condition factor of the sultan fish, leptobarbus hoevenii broodstock farmed in earthen ponds - Sajeenuth Srithongthum; Thumronk Amornsakun; Poramat Musikarun; Pornpanom Promkaew; Au, Hsein Loong; Gunzo Kawamura; Mohammad T. M. Lal; Lim, Leong Seng (Zoology Department, 2020)
The present study was aimed to assess the general health condition of Sultan fish, Leptobarbus hoevenii broodstock through their length-weight relationship (LWR) and relative condition factor (RCF). This broodstock was poly-cultured with the other carp’s species in earthen ponds. Totally, 95 broodstock (35 females and 60 males) were examined in this study. The total length (cm) and body weight (g) ranges of the L. hoevenii broodstock were 32.8 – 43.0 cm and 460 – 1,400 g for the females, while 30.0 – 44.5 cm and 285 – 1,300 g for the males, respectively. The b value of the females was 3.10 (> 3.0), indicating that they have attained positive allometric growth. In opposite, the males and the overall populations have attained negative allometric growth as their b value was 2.66 and 2.92 (< 3.0), respectively. All of these LWRs were significant at α = 0.01 with their correlation coefficient (r) values at 0.88 - 0.90. However, the 95% confidence interval of these b values were in the range of 2.32 – 3.64; they included 3.0 and overlapped each other. This result showed that these b values were not significantly different, indicating that the fish has achieved ideal growth. In addition, the relative condition factors of both females and males have achieved more than 1 (1.04 and 1.01, respectively), indicating that they have achieved their expected weight. Further observation on the LWR of the male L. hoevenii broodstock from the wild is necessary to confirm its optimum b value. Overall, the b value of the broodstock was 2.92 (close to 3), and their RCF value was 0.98 (close to 1). Therefore, the broodstock can be considered in good health condition. However, the influence of poly-culture management on the LWR of this broodstock should be examined in future studies.